Population Pharmacokinetic Model for Ertugliflozin in Healthy Subjects and Patients With Type 2 Diabetes Mellitus. Issue 7 (17th November 2020) - Fediuk, Daryl J.; Zhou, Susan; Dawra, Vikas Kumar; Sahasrabudhe, Vaishali; Sweeney, Kevin
Abstract: Ertugliflozin is a selective sodium‐glucose cotransporter 2 inhibitor approved as an adjunct to diet and exercise to improve glycemic control in adults with type 2 diabetes mellitus (T2DM). A population pharmacokinetic (popPK) model was developed to characterize the pharmacokinetics (PK) of ertugliflozin and quantify the influence of intrinsic (eg, body weight, age, sex, race, estimated glomerular filtration rate [eGFR], T2DM) and extrinsic (eg, food) covariates on the PK parameters of ertugliflozin. The analysis was conducted using data from 15 clinical studies (phases 1‐3) enrolling healthy subjects and patients with T2DM, which included 13, 691 PK observations from 2276 subjects and was performed using nonlinear mixed‐effects modeling. A 2‐compartment popPK model with first‐order absorption and a lag time and first‐order elimination, described the plasma concentration–time profile of ertugliflozin after single and multiple dosing in healthy subjects and in patients with T2DM. Apparent clearance increased with increasing body weight and eGFR, was slightly lower in patients with T2DM and females, and was slightly higher in Asians. Apparent central volume of distribution increased with increasing body weight and was higher in females and Asians. Administration of ertugliflozin with food decreased the absorption rate constant (ka ) and relative bioavailability (F1) compared with fasted. When ertugliflozin was administered without regard to food, estimates of ka and F1 were similar to those for administration with food. The popPK model successfully characterized ertugliflozin exposure in healthy subjects and patients with T2DM. None of the covariates evaluated had a clinically relevant effect on ertugliflozin PK.